Viral Genome Sequencing Proves Nosocomial Transmission of Fatal Varicella. (28th August 2016) - Depledge, Daniel P.; Brown, Julianne; Macanovic, Jasna; Underhill, Gill; Breuer, Judith
Abstract: We report the first use of whole viral genome sequencing to identify nosocomial transmission of varicella-zoster virus with fatal outcome. The index case patient, nursed in source isolation, developed disseminated zoster with rash present for 1 day before being transferred to the intensive care unit (ICU). Two patients who had received renal transplants while inpatients in an adjacent ward developed chickenpox and 1 died; neither patient had direct contact with the index patient.